2021
DOI: 10.1515/npf-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Source of Life or Kiss of Death: Revisiting State-Civil Society Dynamics in India during COVID-19 Pandemic

Abstract: As COVID-19 spread through India, Civil Society Organizations (CSO)s mobilized resources to support the efforts of the Government by playing the role of an active partner in providing social and economic welfare to the affected population. This paper aims to provide a concise overview of the response of civil society to the pandemic situation at the grassroots and policy level. Further, the authors discuss the paradox in demonstrated efficiency and commitment of civil society, which follows a crackdown on civi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Results of this study showed that Uruguayan civil society developed a large number of actions to contribute to food security in the context of the COVID-19 pandemic, in agreement with previous studies conducted in different countries across the world (14)(15)(16)(36)(37)(38)(39)(40) . The large number of organisations that developed activities to contribute to food security indicates that the actions implemented by the Uruguayan government were not enough to contain the negative effects of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of this study showed that Uruguayan civil society developed a large number of actions to contribute to food security in the context of the COVID-19 pandemic, in agreement with previous studies conducted in different countries across the world (14)(15)(16)(36)(37)(38)(39)(40) . The large number of organisations that developed activities to contribute to food security indicates that the actions implemented by the Uruguayan government were not enough to contain the negative effects of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…The main challenge faced by the organisations was related to the lack of funds or supplies, which generated interruptions in their actions or restrictions on their target population. This result is aligned with the work of Tandon & Aravind (36) , who reported a reduction in the resources of Indian civil society organisations from the sixth month of the response due to reduced donations.…”
Section: Discussionsupporting
confidence: 84%
“…The benefit of the ESC is that this can be done even without a request for proposals, which would specifically be focused on a crisis, as discussed above. Regarding specific types of challenges for nonprofits during the COVID-19 pandemic, the literature mentions diminishing financial donations due to the financial pressures donors were facing (Tandon & Aravind, 2021), returning the public funds due to unrealized projects, (Plaček et al, 2022), financial losses and increased expenditures due to the lockdowns (Meyer et al, 2021), and cancelled fundraising events (Shi, 2022). This analysis showed that the ESC offers financial resources to fund volunteering projects promoting solidarity, with various thematic overlaps with the impact of the health and humanitarian crises, and can therefore, potentially be a partial solution for these challenges, though more research is needed.…”
Section: Nonprofits In the Esc And Implications For Future Crisesmentioning
confidence: 99%
“…Civil society worked with health missions of the government to induce behavior change communication in vernacular languages. 57 They raised issues on behalf of the lesser represented groups such as nomadic tribes and unorganized sector workers to ensure adequate health-care provisions for them. 58 Organizations shared recommendations with the government on policy and legal changes to overcome the impact of COVID-19 on specific vulnerable groups.…”
Section: Civil Society Organizationsmentioning
confidence: 99%